MIKROZONASI DAERAH KENDARI DAN SEKITARNYA BERDASARKAN RESPONS TANAH SETEMPAT - Marjiyono, Marjiyono; Soehaimi, Asdani; H. Setiawan, J. (Pusat Survei Geologi, 2007)
As one of the provincial capital city which is growing fast, database of earth sciences is absolutely required In order to develop the secure of Kendari town. Measurement of microtremor in this region aims to know the site response forward ground shacking. The result of microtremor analysis indicates that the distribution of dominant period of H/V ratio of Kendari and its surrounding area is parallel to Kendari bay, and turning south to follow the pattern of Wanggu river. Susceptibility level in this area which is represented by dominant period values is divided into four categories (> 1.5 seconds, 1.5 -1.0 seconds, 1.0- 0.5 seconds, and <0.5 second). Generally, the pronest area coinciding with recent sedimentation area, is around Kendari Bay and along Wanggu river, while towards outside are it is safer. Keyword:microtremor, ground shacking, Kendari